KEPEMIMPINAN SITUASIONAL KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA MENGAJAR GURU SEKOLAH MENENGAH KEJURUAN - Endang Suhardi (Edum Journal, 2019)
The purpose of this study was to determine the effect of Principal Situational Leadership and Work Motivation on Teaching Performance of State Vocational School Teachers in Ex-Kewedanaan Losarang Indramayu Regency. In this study, the measured variable consists of two independent variables with notations (X1) and (X2), and one variable bound by notation (Y). Data collection techniques are a method used to obtain research data. In this case the author uses the data collection techniques as follows: (1) Literature / Documentation Study; (2) Observation; (3) Interview; (4) Questionnaire / Questionnaire. The data analysis used in this study is using statistical regression analysis. This study concludes that: (1) There is a positive and significant influence of the principal's situational leadership on the teaching performance of the Losarang State Vocational School teachers at Ex-Kewedanaan in Indramayu Regency and the magnitude of the effect is 27%. (2) There is a positive and significant influence of work motivation on the teaching performance of the Losarang State Vocational School teachers at Ex-Kewedanaan in Indramayu District and the magnitude of the effect is 28.8%. (3) There is a positive and significant influence on the principal's situational leadership and work motivation simultaneously on the teaching performance of the Losarang State Vocational School teachers at the Ex-Kewedanaan in Indramayu District and the magnitude of the effect is 41.3%.